The unofficial guide to Windows XP - Toot, Michael (Wiley Pub., 2006)
Microsoft Windows XP SP2 may be a robust and flexible operating system, but to use it with confidence you'll need to know its quirks and shortcuts. Find out what the manual doesn't always tell you in this insider's guide to using Windows XP in the real world. What's the best way to handle security? How do you set up a network?